Decay behavior and stability of free radicals of silk fibroin with alkali/urea pretreatment induced by electron beam irradiation. (November 2020) - Zhang, Hao; Tian, Feng; Lin, Haitao; Shen, Rongfang; Liu, Weihua; Huang, Yuying; Tang, Zhongfeng
Highlights: A simple pretreatment method to improve the yield and stability of the free radicals was reported. Crystalline transformation, compacted spatial structure are responsible for high concentration and stability. Radical concentration increased 10 times at 25 kGy. The half-life time of free radicals is 10 times. Abstract: Silk fibroin determines the perseverance of silk-based materials. The samples of silk fibroin were pretreated combined alkali/urea system with rapid freezing in liquid nitrogen. The structural changes of unpretreated and pretreated silk fibroins were investigated by XRD, SAXS and FTIR. The results indicate that part of the amorphous region was transformed into silk-II crystalline structure, and the radius of gyration decreased due to the folding of molecular chains by hydrogen bonds. The free radicals of unpretreated and pretreated silk fibroin induced by electron beam irradiation were studied by electron spin resonance (ESR). The results indicate that the radical concentration increased by 10 times at 25 kGy and attained 8.04*10 19 spins·g −1 at 50 kGy after pretreatment, which is comparable to the saturated radical concentration of unpretreated silk fibroin above 200 kGy. And the half-life time of free radicals is 10 times longer than that of the unpretreated samples. The higher stability of the free radicals is considered to be related to the protein structure changes induced by pretreatment and this can provide convenience for silk irradiation grafting. The new pretreatment method may provide inspiration for designing protein structures to regulate free radical formation.